Male Obesity Associated Gonadal Dysfunction and the Role of Bariatric Surgery - Sultan, Sana; Patel, Ameet G.; El-Hassani, Shamsi; Whitelaw, Benjamin; Leca, Bianca M.; Vincent, Royce P.; le Roux, Carel W.; Rubino, Francesco; Aywlin, Simon J. B.; Dimitriadis, Georgios K. (Frontiers in Endocrinology, 2020)
Obesity is an ever growing pandemic and a prevalent problem among men of reproductive age that can both cause and exacerbate male-factor infertility by means of endocrine abnormalities, associated comorbidities, and direct effects on the precision and throughput of spermatogenesis. Robust epidemiologic, clinical, genetic, epigenetic, and preclinical data support these findings. Clinical studies on the impact of medically induced weight loss on serum testosterone concentrations and spermatogenesis is promising but may show differential and unsustainable results. In contrast, extensive literature has demonstrated that weight loss after bariatric surgery is correlated with an increase in serum testosterone concentrations that is superior than that obtained with only lifestyle modifications, supporting a further metabolic benefit from surgery that may be specific to the male reproductive system. The data on sperm and semen parameters is controversial to date. Emerging evidence in the burgeoning field of genetics and epigenetics has demonstrated that paternal obesity can affect offspring metabolic and reproductive phenotypes by means of epigenetic reprogramming of spermatogonial stem cells. Understanding the impact of this reprogramming is critical to a comprehensive view of the impact of obesity on subsequent generations. Furthermore, conveying the potential impact of these lifestyle changes on future progeny can serve as a powerful tool for obese men to modify their behavior. Healthcare professionals treating male infertility and obesity need to adapt their practice to assimilate these new findings to better counsel men about the importance of paternal preconception health and the impact of novel non-medical therapeutic interventions. Herein, we summarize the pathophysiology of obesity on the male reproductive system and emerging evidence regarding the potential role of bariatric surgery as treatment of male obesity-associated gonadal dysfunction.